Analysis of Energy Management of Garnesa Electric Car Based Numerical Simulation Modeling - Bidya Nur Habib; Agung Prijo Budijono (Journal of World Conference (JWC), 2019)
Designing an electric car to compete with ESCC should be guided by Vehicle Construction and Stability. One of the areas to consider when designing at the research and development stage is the Mechanical Mechanical System (Rotational Mechanical System). These systems include, wheels, transmissions (gear connections), electric motor rotors and shafts. The purpose of this study was to determine the effect of vehicle energy management on driver driving strategies during the ESCC competition. This is based on Wheel Mechanical System modeling, Dynamic System Analysis and Free Body Diagram. The method used is based on Numerical Simulation. The data parameters used are based on independent variables and control variables. The independent variable of this study is the angular velocity (V?), linear velocity (v) of the vehicle, friction coefficient value (B), shaft stiffness (K), wheel diameter, gear diameter, wheel mass and moment inertia of the wheel. Control variables is technical regulation of ESCC Urban Concept. This Numerical Simulation Test is to determine the required electrical power, travel time and distance of the vehicle. The results showed that the energy needed by GARNESA electric car with an average speed selection of 9.42 m /s based on a maximum speed of 10.15 m /s and a minimum speed of 8.70 m /s requires the amount of power 248.15 Watt. Travel time is 180 seconds in one lap. The distance obtained is 1357 m. Driving strategy based on average speed of 9.42 m /s consumes less power and the distance obtained will be more far.